Characteristics of Soil Nematode Communities in Pure Populus hopeiensis Forests in the Loess Hilly Region and Their Responses to Precipitation - Yani Hu; Jiahao Shi; Fangfang Qiang; Changhai Liu; Ning Ai (Agronomy, 2025)
To clarify the response mechanisms of soil nematodes as bioindicators of ecosystem health to precipitation variations in loess hilly forests, this study investigated soil nematodes in pure Populus hopeiensis forests across different precipitation gradients in Wuqi County. Through soil physicochemical analysis and high-throughput sequencing of soil nematodes, we analyzed the characteristics of soil nematode communities and their responses to precipitation variation. The results demonstrated the following: (1) Dominant genera and trophic groups of soil nematodes were significantly influenced by precipitation, with Acrobeloides prevailing across all gradients while Paratylenchus reached maximum abundance (26.8%) in moderate precipitation zones. (2) Bacterivorous nematodes prevailed in both low- and high-precipitation zones, while herbivorous nematodes constituted the highest proportion in moderate precipitation zones. The abundances of herbivorous and fungivorous nematodes exhibited an initial increase followed by a decrease with rising precipitation, whereas predatory–omnivorous nematodes displayed the opposite trend. (3) The Chao1 and Shannon indices of soil nematodes initially increased and then decreased with increasing precipitation, reaching a peak in the Jinfoping site. Moreover, there were significant differences in nematode community structure among different precipitation gradients. (4) Redundancy analysis and PLS-PM modeling identified soil water content (SWC), total nitrogen (TN), and capillary water holding capacity (CWHC) as key drivers of nematode communities. Precipitation indirectly regulated nematode functionality by modifying soil physicochemical properties and microbial activity. (5) Ecological function analysis revealed bacterial-dominated organic matter decomposition (Nematode Channel Ratio, NCR > 0.75) in the Changcheng and Baibao sites, contrasting with fungal channel predominance (NCR < 0.75) in Jinfoping. This research elucidates the mechanism whereby precipitation drives nematode community divergence through regulating soil physicochemical properties and microbial activity. The findings provide scientific basis for soil biodiversity conservation and ecological restoration benefit assessment in regional ecological restoration projects, and soil health management and sustainable land use in agricultural ecosystems.